Management of Discolored Failure Root Canal-Treated Upper Lateral Incisor - Rozainah, Nik Abdul Ghani Nik (Case Rep Dent, 2020)
Root canal treatment failure can be determined based on a patient's complaint and on the basis of clinical examination and radiographic findings. Most of the signs and symptoms for the failure are pain and discomfort, swelling and sinus formation at the surrounding soft tissue, and discoloration of the subjected tooth. Factors such as mechanical perforation during the procedures, overfilled or underfilled root canal, and missed or unfilled canals are the main factors for the failure outcome. This case report presents a discolored and infected upper lateral incisor which was previously root canal treated. The tooth was successfully managed under nonsurgical and surgical retreatment followed by an internal bleaching and full porcelain veneer. Apical tissue healing and acceptable tooth appearance was observed during a 12-month review.